Online payment procedure involving mobile phone network infrastructure and devices - Mantoro, Teddy; Milisic, Admir; Ayu, Media Anugerah (2011)
With widespread Internet usage, e-commerce became common way of conducting business. Money transactions and payments online are an ever increasing trend. Unfortunately, problems in terms of security arise as well. Most of the potential consumers choose to abstain from online money transfer due to the privacy concerns. In order to strengthen the trust and gain their acceptance, security improvements are required. At the same time, however, solution needs to be convenient, entailing ease of use and higher mobility. For this purpose, involvement of mobile phone network is suggested to support online payment procedure. Mobile phone’s SIM card is convenient for safely storing security parameters essential for secured money transaction. SIM card-equipped phone becomes secure entity compulsory for getting access to client side PC application for money transfer. Ease of use, portability and mobility are guaranteed while parameters such as cryptography keys or credit card numbers are securely updated trough the mobile phone network.